The Effect of Sharia Compliance, Attitudes, Satisfaction and Perceived Usefulness on Continued Intention to Use Sharia Digital Banking: A Study of Muslim Customer Behavior - Taujiharrahman, Darma; Alfianto, Achmad Nur (PT FORMOSA CENDEKIA GLOBAL, 2024)
In activities related to financial services, a Muslim has a tendency to choose Shariah-compliant services. The presence of digital banking services will certainly not escape this tendency but in a rational view, this tendency is often challenged. For this reason, research is needed that relates the behavior of a Muslim in choosing digital banking services that not only comply with sharia provisions but also provide benefits that can be felt directly. This study integrates the factors recognized in technology continuance theory with the prevailing values in Muslim behavior to provide results that match the digital characteristics of Islamic banking. Data were collected from 183 Muslim users of Islamic digital banking services in Java, Indonesia and then tested with structural equation modeling (SEM). The research findings show that sharia compliance and perceived usefulness directly have no effect on continuance intention to use Islamic digital banking services, but indirectly through attitude mediation, these two factors have a significant effect. In the direct effect, satisfaction is the most determinant factor in influencing continuance intention to use, while perceived usefulness is the most determinant factor in influencing attitude. Then in the indirect effect, attitude has a full mediation role on the effect of perceived usefulness on continuance intention to use, and partial mediation of the effect of sharia compliance on continuance intention to use